1989
DOI: 10.1007/bf00002203
|View full text |Cite
|
Sign up to set email alerts
|

Larval biology of butterflyfishes (Pisces, Chaetodontidae): what do we really know?

Abstract: SynopsisRelatively little is known of the pelagic portion of the life history of butterflyfishes . Eggs are small (<1 mm), pelagic and hatch in less than 30 hours . Most species pass through a so-called tholichthys larval interval characterized by elaborate, distinctive head spination : Coradion larvae have different head spination . While older chaetodontid larvae can be identified by adult characters, young (preflexion) larvae generally cannot now be identified below family . In tropical plankton studies cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Another explanation is that coral‐feeding wrasses have a much higher recruitment rate, which may facilitate re‐colonization following a major disturbance event. In general, larval butterflyfishes are poorly represented in the plankton (Leis, 1989). In a 2·5 year recruitment study, butterflyfishes were found to have some of the lowest recruitment rates on near‐shore reefs in Kimbe Bay (Srinivasan & Jones, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that coral‐feeding wrasses have a much higher recruitment rate, which may facilitate re‐colonization following a major disturbance event. In general, larval butterflyfishes are poorly represented in the plankton (Leis, 1989). In a 2·5 year recruitment study, butterflyfishes were found to have some of the lowest recruitment rates on near‐shore reefs in Kimbe Bay (Srinivasan & Jones, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…At this larger spatial scale, it is likely that stochastic variation in larval supply and patterns of recruitment contributes to observed patterns of distribution and abundance (Bell et al , 1985). Ascertaining the importance of larval supply in driving patterns of abundance for butterflyfishes, however, has proved very difficult (Leis, 1989) due to the rarity of butterflyfishes in field collections of larval fishes (Leis & Miller, 1976; Leis, 1982; Leis & Goldman, 1984; Young et al , 1986). Despite potential differences in larval supply, this study shows that overall abundance of butterflyfishes, as well as the individual abundance of most obligate hard‐coral feeders, is strongly correlated with percentage cover of scleractinian corals.…”
Section: Discussionmentioning
confidence: 99%
“…Blum (1988) described six characters that diagnose a monophyletic Chaetodontidae: (1) sequential articulation between the first dorsal pterygiophore, the supraneural bones, and the supraoccipital crest; (2) pleural rib laminae that extend forward from the medial edges of the descending shafts; (3) pleural ribs of exceptional length; (4) presence of a ligament that connects the anterior edge of the second post-cleithrum to the basipterygium, just anterior to the origin of the pelvic spine; (5) the two anterior branchiostegals (or, if only five are present, the single anterior branchiostegal) do not make contact with the ceratohyal; (6) specialized larval stage known as a tholichthys larva. This sixth character, the presence of a tholichthys larval stage (sensu Burgess, 1978), has been questioned by some authors (e.g., Leis, 1989) because some chaetodontids do not share the typical tholichthys form and some nonchaetodontids (e.g., scatophagids) have similar larval morphology. Regardless of the utility of using the tholichthys larval stage as a synapomorphy of the family, the monophyly of the family is still supported by the first five characters presented above.…”
Section: Phylogenetic Methodsmentioning
confidence: 99%